Prediction of MRI erosive progression: a comparison of modern imaging modalities in early rheumatoid arthritis patients. Issue 1 (10th November 2010) - Bøyesen, Pernille; Haavardsholm, Espen A; van der Heijde, Désirée; Østergaard, Mikkel; Hammer, Hilde Berner; Sesseng, Sølve; Kvien, Tore K
Abstract : Objectives: To examine the associations between modern imaging modalities and joint damage measured as 1-year MRI erosive progression, in early rheumatoid arthritis (RA) patients. Methods: 84 RA patients with disease duration of less than 1 year were included in this inception cohort. Patients were evaluated at baseline, 3, 6 and 12 months by core measures of disease activity, MRI and ultrasound grey-scale (USGS) of inflammation, conventional radiography and digital x-ray radiogrammetry (DXR) bone mineral density (BMD) of cortical hand bone. Results: 53 of the 79 patients (67%) who completed the follow-up had MRI erosive progression (dependent variable). USGS and MRI bone marrow oedema (BME) were in multivariate analyses independent predictors of 1-year MRI erosive progression. There was a trend towards higher MRI synovitis score and 3-month DXR BMD loss in patients developing MRI erosions. On an individual level, USGS inflammation, MRI synovitis and MRI BME also somewhat better predicted outcome than rheumatoid factor, anticitrullinated protein antibodies and disease activity score 28. Conclusions: USGS inflammation and MRI BME were independent predictors of MRI erosive progression in early RA patients on a group level. The exact prognosis of the individual patients could not be determined by imaging alone.